An Injectable IPN Nanocomposite Hydrogel Embedding Nano Silica for Tissue Engineering Application - Ali Kakapour; Saied Nouri Khorasani; Shahla Khalili; Mahshid Hafezi; Mehdi Sattari‐Najafabadi; Mahsa Najarzadegan; Samin Saleki; Shadab Bagheri‐Khoulenjani (Macromolecular Materials and Engineering)
Abstract Gelatin methacrylate (GM) and sodium alginate (SA) are two biomaterials that have been widely employed in tissue engineering, particularly in 3D bioprinting. However, they have some drawbacks including undesirable physico‐mechanical properties and printability, hindering their application. This work developed an interpenetrating polymeric network (IPN) of GM and SA reinforced with silica nanoparticles (SNPs) to deal with hydrogels’ drawbacks. Besides, for cross‐linking, visible light is used as an alternative to UV light to prevent disruptions in cellular metabolism and immune system reactions. Four GM/SA/SNP hydrogels different in SNPs concentration (0, 0.5, 1, and 2 w/w%) are studied. The performance of the hydrogels is evaluated in terms of physico‐mechanical properties (viscoelasticity, compressive modulus, degradation, and swelling), rheological properties, and biological properties (fibroblast cell growth and adhesion, and MTT assay). The results demonstrated that the GM/SA/SNP hydrogel with 1% SNPs provided desirable physical (645% swelling and 59.3% degradation), mechanical strength (270 kPa), rheological (tan δ of almost 0.14), and biological performances (≈98% viability after 3 days) while maintaining appropriate printability. The findings suggest that the GM/SA/SNP hydrogel holds great potential for applications in soft tissue regeneration.